Applications of Selectfluor in Organic Synthesis-A Quadrennial Update - Varala, Ravi; Seema, Vittal; Kamsali, Murali Mohan Achari; Hussein, Mohamed; Alam, Mohammed Mujahid (Current Organic Chemistry, 2025)
Selectfluor, bis(tetrafluoroborate)[1-chloromethyl-4-fluoro-1,4-diazoniabicyclo-[2.2.2] octane] is an extraordinarily stable solid with exceptional properties, such as strong solubility and stability in polar solvents, minimal toxicity, excellent thermal stability, and utility as an oxidant. One of the electrophilic fluorinating compounds that is most frequently employed in fluorination reactions is Selectfluor. In this mini-review, we have briefly updated the various applications of Selectfluor in organic synthesis, particularly in C-C, C-heteroatom and heteroatom-heteroatom bond formation reactions from mid-2020 to date. In addition to these, Selectfluor found useful in heterocyclic ring formations, demethylation, deoxygenation and other miscellaneous reactions. The results that have been published thus far show how extraordinarily promising Selectfluor-mediated organic molecule skeleton assembly events can be. Visible light, electrochemical, and nano-based reactions still have a lot of room for growth and application, despite the noteworthy advances in these domains. The compilation is subdivided based on the type of reaction/function of Selectfluor organic transformation.
Keywords: Selectfluor